1974
DOI: 10.1073/pnas.71.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Three Nucleotide Polymerases by Rifamycin Derivatives

Abstract: It is possible to design rifamycin derivatives which can distinguish between viral RNA-instructed DNA polymerase and other nucleotide polymerases.The discovery by Baltimore (1) and Temin and Mizutani (2) of a DNA polymerase which utilizes RNA as its template, and the enzyme's relatively specific association with oncogenic viruses, has opened a new area of research on possible chemotherapy for virus-related cancers. Certain rifamycin derivatives serve as effective antibiotics by inhibiting the bacterial DNA-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1974
1974
2000
2000

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…RNA-dependent DNA polymerase activity partially purified from a transformed line of mouse embryo cells has been reported (24). Since only RSV-infected cells were used in the studies described in this report, the inhibition of RSV DNA polymerase activity by R-82 was tested and compared with other rifamycin derivatives (Table 1).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…RNA-dependent DNA polymerase activity partially purified from a transformed line of mouse embryo cells has been reported (24). Since only RSV-infected cells were used in the studies described in this report, the inhibition of RSV DNA polymerase activity by R-82 was tested and compared with other rifamycin derivatives (Table 1).…”
Section: Downloaded Frommentioning
confidence: 99%
“…A number of new rifamycin derivatives synthesized in this laboratory have been shown to be inhibitors of murine leukemia virus RNAdependent DNA polymerase (24). One of these compounds, rifazone-82 (R-82), also selectively inhibits the growth of Rous sarcoma virus (RSV)-transformed chicken embryo cells in culture and prevents virus-induced focus formation (2).…”
mentioning
confidence: 99%
“…In addition, we have tested rifazone-82 (R-82), a new rifamycin which is to date the most selective inhibitor of viral RNAdirected DNA polymerase in vitro (6,21). We find that at low concentrations (3-10 gg,ml), R-82 can selectively inhibit the growth of transformed cells and prevent focus formation while allowing the normal cell growth and function to continue.…”
mentioning
confidence: 99%
“…The in vitro demonstration that RNAdirected 'DNA polymerase is inhibited by the action of some of these derivatives (6)(7)(8)(9)(10)(11)(12)(13) has raised the possibility that the drugs may inhibit focus formation by inhibiting the activity of RNA-directed DNA polymerase. Smith et al have shown recently that those rifamycin derivatives that are toxic to leukemic human leukocytes are also those that inhibit RNAdirected DNA polymerase best in vitro (14).…”
mentioning
confidence: 99%
“…Two compounds are derivatives of rifamycin SV, well characterized as to their potent inhibition of reverse transcriptase and activity against Rauscher virus-induced splenomegaly (25,28): compound no. 120, 2,6-dimethyl benzyl 4-demethyl rifampin ( (Fig.…”
mentioning
confidence: 99%